2014
DOI: 10.1371/journal.pone.0103660
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Usefulness of Urinary Biomarkers for the Identification of Cyclosporine A-Induced Nephrotoxicity in a Rat Model

Abstract: The main side effect of cyclosporine A (CsA), a widely used immunosuppressive drug, is nephrotoxicity. Early detection of CsA-induced acute nephrotoxicity is essential for stop or minimize kidney injury, and timely detection of chronic nephrotoxicity is critical for halting the drug and preventing irreversible kidney injury. This study aimed to identify urinary biomarkers for the detection of CsA-induced nephrotoxicity. We allocated salt-depleted rats to receive CsA or vehicle for 7, 14 or 21 days and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
1
13
0
2
Order By: Relevance
“…These data lead to the conclusion that the preexistence of hypertension in our model could not be accounted for glomerular and tubular remodeling in the early phase of ADR nephropathy. Other studies have shown that the up-regulation of vimentin expression was observed in the renal tubules and interstitial areas in cyclosporine A-induced nephrotoxicity [31,32]. Since vimentin is used as a marker of tubulointerstitial injury and epithelial-mesenchymal transition, the neoexpression of vimentin in the proximal tubules is an unequivocal signal of injury and regeneration in these areas [31,33].…”
Section: Discussionmentioning
confidence: 97%
“…These data lead to the conclusion that the preexistence of hypertension in our model could not be accounted for glomerular and tubular remodeling in the early phase of ADR nephropathy. Other studies have shown that the up-regulation of vimentin expression was observed in the renal tubules and interstitial areas in cyclosporine A-induced nephrotoxicity [31,32]. Since vimentin is used as a marker of tubulointerstitial injury and epithelial-mesenchymal transition, the neoexpression of vimentin in the proximal tubules is an unequivocal signal of injury and regeneration in these areas [31,33].…”
Section: Discussionmentioning
confidence: 97%
“…23,29,30 We aimed to ascertain the effects on these markers in CsA-treated rats given 5 ng/kg 2AMD. The Figure 4 immunoblots show ECM and lysate fractions reacted for fibronectin using histone 3 as loading control for the ECM fractions or for vimentin using GAPDH as loading control for lysates.…”
Section: Resultsmentioning
confidence: 99%
“…inulin clearance test, creatinine clearance test, and analysis of urinary biomarkers (e.g. neutrophil gelatinase-associated lipocain, kidney injury molecule-1, N-acetyl-β-D-glucosaminidase) (33)(34)(35). For a more accurate evaluation of renal function, one of the supplementary methods mentioned above may be performed as well; however, monitoring serum BUN and creatinine levels alone is quite an accurate measure of renal function and a meaningful method in a clinical setting (6,36).…”
Section: Histological Manifestation Of the Kidneys After Transplantmentioning
confidence: 99%